Aluminum alloy, shell and terminal equipment
By adding Si, MG, X elements, and CU to aluminum alloy, the enhanced phase and high -mode volume are formed, the problem of low elasticity of aluminum alloy and poor anode appearance effects, and the high elasticity suitable for terminal equipment is realized. Modern and good anode appearance effects.
Patent Information
- Application Number
- CN202310886595.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-01-21
AI Technical Summary
The elastic modulus of existing aluminum alloys is low, and free silicon ions are dissolved and resolved during the anodization process due to the high-mode phase SiC dissolution and decomposition of free silicon ions, resulting in poor appearance and failure to be applied to terminal equipment.
By adding Si elements and Mg elements to the aluminum alloy to form the strengthening phase Mg2Si, the elastic modulus is increased, and by adding X elements (such as Ni, B, Li) and Al elements to form a high-modulus AlX phase, combined with Cu elements to form an anode. The soluble AlXCu phase improves the elastic modulus of aluminum alloy and the appearance of the anode.
The high elastic modulus of aluminum alloy and good anode appearance effects are achieved, so that it is suitable for the shell material of the terminal equipment.
Smart Images

Figure BDA0004347572490000051 
Figure BDA0004347572490000061 
Figure BDA0004347572490000071
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of aluminum alloys, and in particular to an aluminum alloy, a housing, and a terminal device. Background Art
[0002] The shells used in existing terminal devices usually need to be thinner and lighter, which reduces the rigidity of the shells. Therefore, the shells of terminal devices need materials with higher elastic modulus. The elastic modulus of existing aluminum alloys is usually very low. Although the elastic modulus of aluminum alloys can be improved by adding high-modulus SiC to the aluminum alloys, the high-modulus SiC will dissolve and release free silicon ions during the anodizing process of the aluminum alloys. The free silicon ions adsorbed on the surface of the aluminum alloy will cause the anodized film to turn black, making it impossible for the aluminum alloy to be anodized, resulting in the poor anode appearance of the shells processed by the aluminum alloy, which in turn makes the aluminum alloy unable to be used in terminal devices. Summary of the invention
[0003] The purpose of the embodiments of the present application is to provide an aluminum alloy, a shell and a terminal device. The aluminum alloy has a high elastic modulus and can be anodized, so that the shell formed by the aluminum alloy has a good anode appearance effect and can be applied to terminal equipment.
[0004] An embodiment of the present application provides an aluminum alloy, wherein the components of the aluminum alloy include, based on the mass of the aluminum alloy: 0.7%≤Mg≤1.1%, 0.5%≤Si≤1.1%, 0.5%≤Cu≤4.5%, 0<Mn≤0.9%, 0≤X<6%, 85.7%≤Al≤98.3%, and the total content of inevitable impurity elements is ≤1.0%, wherein the X element is selected from at least one of the Ni element, the B element, and the Li element.
[0005] In the aluminum alloy provided in the embodiment of the present application, the added Si element and the Mg element can form a strengthening phase Mg2Si, and the strengthening phase Mg2Si can improve the elastic modulus of the aluminum alloy. At the same time, the added Si element will not precipitate free silicon ions during the anodizing process, thereby avoiding the problem that the aluminum alloy cannot be anodized due to the addition of the high modulus phase SiC, and ensuring that the aluminum alloy of the embodiment of the present application has the effect of anodizing. In addition, by adding the X element, the X element can generate a high modulus AlX phase with the Al element in situ, thereby further improving the elastic modulus of the aluminum alloy. At the same time, the high modulus AlX phase can be completely dissolved in the anodizing of the aluminum alloy, and does not affect the anode appearance of the aluminum alloy. By adding Cu to the aluminum alloy, Cu can generate an anode-soluble high modulus AlXCu phase with the high modulus AlX phase, which is beneficial to further improve the elastic modulus of the aluminum alloy. In addition, the aluminum alloy has a high Cu content. On the one hand, it can significantly improve the elastic modulus of the aluminum alloy by increasing the proportion of high modulus AlXCu phase. On the other hand, with sufficient Cu element addition, it can maintain low Mg and Si contents. While ensuring that Mg and Si can form a strengthening phase Mg2Si to improve the elastic modulus of the aluminum alloy, it can also avoid the problem of a decrease in the high-brightness anodizing effect of the aluminum alloy due to the formation of a large amount of insoluble Mg2Si phase due to excessive Mg and Si content. This is beneficial to improving the anode appearance of the shell made of aluminum alloy. The shell made of the aluminum alloy has a better anode appearance when used in terminal equipment.
[0006] In addition, the Mn element added to the aluminum alloy can hinder the nucleation and growth process of the recrystallization of the aluminum alloy, have a certain strengthening effect on the aluminum alloy, and can also improve the yield strength, tensile strength and elongation of the aluminum alloy, thereby helping the aluminum alloy to exhibit stronger toughness and reduce the sensitivity to stress corrosion cracking.
[0007] In a possible implementation, X is Ni, and the mass ratio of Cu to Ni is: Cu:Ni=(0.75-2.0):(1.0-2.0). Within this composition mass ratio range, the aluminum alloy can obtain an excellent elastic modulus, as well as good yield strength, tensile strength and elongation, so that the aluminum alloy exhibits toughness and can obtain a bright anode appearance.
[0008] In a possible implementation, X is element B, and the mass ratio of Cu to element B is: Cu:B=(0.75-2.5):(1.0-2.0). Within this mass ratio range of components, the aluminum alloy can obtain an excellent elastic modulus, as well as good yield strength, tensile strength and elongation, so that the aluminum alloy exhibits strong toughness and can obtain a bright anode appearance.
[0009] In a possible implementation, X is Li element, and the mass ratio of Cu to Li element is: Cu:Li=(0.75-2.0):(1.0-2.0). Within this composition mass ratio range, the aluminum alloy can obtain an excellent elastic modulus, as well as good yield strength, tensile strength and elongation, so that the aluminum alloy exhibits strong toughness and can obtain a bright anode appearance.
[0010] In a possible implementation, X is Ni, B and Li, and the mass ratio of Cu to Ni, B and Ni is: Cu: Ni: B: Li = (0.75-2.0): (0.6-1.2): (0.2-0.4): (0.4-0.7). Within this mass ratio range of components, the aluminum alloy can obtain an excellent elastic modulus, as well as good yield strength, tensile strength and elongation, so that the aluminum alloy exhibits toughness and can obtain a bright anode appearance.
[0011] In a possible implementation, the aluminum alloy includes an Al matrix and second phase particles dispersed in the Al matrix, the Al matrix is formed of Al element, and the second phase particles are formed of at least two elements selected from the group consisting of Al element, Mg element, Si element, Cu element, Mn element and X element.
[0012] In a possible embodiment, in the cross section of the aluminum alloy, within 0.05 mm 2 Within the cross-sectional area, the number of second phase particles with a diameter of ≥10 μm is ≤20, which can ensure that the second phase particles are completely dissolved during anodizing and do not affect the high-brightness anode appearance of the aluminum alloy.
[0013] In a possible implementation manner, the unavoidable impurity elements include at least one of Ti, Cr and Fe.
[0014] In a possible implementation, 0.5%≤Cu≤3.0%, 1.0%≤X≤5.5%. In this composition range, the aluminum alloy can obtain excellent elastic modulus, as well as good yield strength, tensile strength and elongation, so that the aluminum alloy exhibits strong toughness.
[0015] In a possible implementation, 0.6% ≤ Cu ≤ 2.0%, 1.0% ≤ X ≤ 2.0%. In this composition range, the aluminum alloy can obtain excellent elastic modulus, as well as good yield strength, tensile strength and elongation, so that the aluminum alloy exhibits strong toughness and can obtain a bright anode appearance.
[0016] The embodiment of the present application also provides a shell, which is made of the above-mentioned aluminum alloy.
[0017] This embodiment also provides a terminal device, including a display screen and a housing as described above, wherein the display screen is mounted on the housing.
[0018] In a possible implementation, the terminal device is a mobile phone, and the shell is the middle frame of the mobile phone; or, the terminal device is a tablet computer, and the shell is the middle frame of the tablet computer; or, the terminal device is a computer, and the shell is the shell of the computer. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0020] Anodic oxidation: refers to a material protection technology in which an oxide film is formed on the surface of a metal material by applying an external anodic current in an electrolyte solution; for example, an aluminum alloy is placed in an electrolyte solution and an external anodic current is applied to form an oxide film on the surface of the aluminum alloy.
[0021] The embodiment of the present application provides a terminal device, the terminal device includes a display screen and a housing, and the display screen is mounted on the housing. The terminal device may be a mobile phone, a tablet computer, a computer, a wearable product, or other device. Exemplarily, the terminal device is a mobile phone, in which case the housing may be the middle frame of the mobile phone. The terminal device is a tablet computer, in which case the housing may be the middle frame of the tablet computer. The terminal device is a computer (Personal Computer, PC), in which case the housing may be the housing of the computer (PC housing).
[0022] The shell can be made by aluminum alloy processing. In one embodiment of the present application, an aluminum alloy is provided. The composition of the aluminum alloy includes, by weight of the aluminum alloy, 0.7%≤Mg≤1.1%, 0.5%≤Si≤1.1%, 0.5%≤Cu≤4.5%, 0<Mn≤0.9%, 0≤X<6%, 85.7%≤Al≤98.3%, and the total content of inevitable impurity elements is ≤1.0%, wherein the X element is selected from at least one of the B element, the Li element, and the Ni element.
[0023] Exemplarily, based on the mass of the aluminum alloy, the content of the Mg element in the aluminum alloy may be 0.7%, 0.9%, 1.1%, and any values between the above values. Based on the mass of the aluminum alloy, the content of the Si element in the aluminum alloy may be 0.5%, 0.7%, 1.1%, and any values between the above values. Based on the mass of the aluminum alloy, the content of the Cu element in the aluminum alloy may be 0.5%, 0.75%, 1.0%, 1.5%, 2.0%, 2.5%, 4.5%, and any values between the above values. Based on the mass of the aluminum alloy, the content of the Mn element in the aluminum alloy may be 0.06%, 0.4%, 0.9%, and any values between the above values. Based on the mass of the aluminum alloy, the content of the X element in the aluminum alloy may be 0%, 2.0%, 4.0%, 5.0%, 5.9%, and any values between the above values. Calculated by the mass of the aluminum alloy, the content of Al element in the aluminum alloy may be 85.7%, 93.33%, 93.35%, 94.13%, 94.61%, 95.36%, 95.30%, 95.33%, 96.33%, 96.34%, 96.37%, 97.34%, 98.18%, 98.3%, and any values between the above values.
[0024] In the aluminum alloy formula provided in the embodiment of the present application, by adopting the aluminum alloy formula, on the one hand, the aluminum alloy can have the effect of being anodized, so that the shell made of the aluminum alloy has a better anode appearance effect, and on the other hand, the elastic modulus of the aluminum alloy can be greatly improved, thereby facilitating the improvement of the elastic modulus of the shell made of the aluminum alloy. Specifically, the elastic modulus of the existing aluminum alloy is usually 68-70GPa, and in the aluminum alloy of the embodiment of the present application, the added Si element and the Mg element can form a strengthening phase Mg2Si, which can improve the elastic modulus of the aluminum alloy. At the same time, the added Si element will not precipitate free silicon ions during the anodization process, avoiding the problem that the aluminum alloy cannot be anodized due to the addition of the high modulus phase SiC, and ensuring that the aluminum alloy of the embodiment of the present application has the effect of being anodized. In addition, by adding the X element, the X element can generate a high modulus AlX phase with the Al element in situ, thereby facilitating the further improvement of the elastic modulus of the aluminum alloy, and the high modulus AlX phase can be completely dissolved in the anodization of the aluminum alloy, without affecting the anode appearance of the aluminum alloy. By adding Cu to the aluminum alloy, Cu can generate an anode-soluble high modulus AlXCu phase with a high modulus AlX phase, which is beneficial to further improve the elastic modulus of the aluminum alloy. In addition, the aluminum alloy has a high Cu content. On the one hand, it can significantly improve the elastic modulus of the aluminum alloy by increasing the proportion of the high modulus AlXCu phase. On the other hand, when sufficient Cu elements are added, the Mg content and Si content can be kept low. While ensuring that Mg and Si can form a strengthening phase Mg2Si to improve the elastic modulus of the aluminum alloy, it can also avoid the problem of a decrease in the high-brightness anodizing effect of the aluminum alloy due to the formation of a large amount of insoluble Mg2Si phase due to excessive Mg and Si content, which is beneficial to improve the anode appearance of the shell made of aluminum alloy. When the shell made of the aluminum alloy is used in terminal equipment, it has a good anode appearance.
[0025] In addition, the Mn element added to the aluminum alloy can hinder the nucleation and growth process of the recrystallization of the aluminum alloy, have a certain strengthening effect on the aluminum alloy, and can also improve the yield strength, tensile strength and elongation of the aluminum alloy, thereby helping the aluminum alloy to exhibit stronger toughness and reduce the sensitivity to stress corrosion cracking.
[0026] Among them, in some possible implementations, the aluminum alloy can be further controlled to have 0.5% ≤ Cu ≤ 3.0%, and 1.0% ≤ X ≤ 5.5%. Under this composition range, the aluminum alloy can obtain excellent elastic modulus, as well as good yield strength, tensile strength and elongation, so that the aluminum alloy exhibits strong toughness.
[0027] In some possible implementations, the aluminum alloy can be further controlled to have 0.6% ≤ Cu ≤ 2.0% and 1.0% ≤ X ≤ 2.0%. Under this composition range, the aluminum alloy can obtain an excellent elastic modulus, as well as good yield strength, tensile strength and elongation, so that the aluminum alloy exhibits strong toughness and can obtain a bright anode appearance.
[0028] In addition, in some possible implementations, in the aluminum alloy, X is Ni element, and the mass ratio of Cu to Ni element is controlled to be: Cu: Ni = (0.75-2.0): (1.0-2.0). Under this composition mass ratio range, the aluminum alloy can obtain excellent elastic modulus, as well as good yield strength, tensile strength and elongation, so that the aluminum alloy exhibits strong toughness and can obtain a bright anode appearance effect.
[0029] In some possible implementations, in the aluminum alloy, X is the B element, and the mass ratio of Cu to B is controlled to be: Cu:B=(0.75-2.5):(1.0-2.0). Within this composition mass ratio range, the aluminum alloy can obtain an excellent elastic modulus, as well as good yield strength, tensile strength and elongation, so that the aluminum alloy exhibits toughness and can obtain a bright anode appearance.
[0030] In some possible implementations, in the aluminum alloy, X is the Li element, and the mass ratio of Cu to Li is controlled to be: Cu: Li = (0.75-2.0): (1.0-2.0). Within this composition mass ratio range, the aluminum alloy can obtain an excellent elastic modulus, as well as good yield strength, tensile strength and elongation, so that the aluminum alloy exhibits strong toughness and can obtain a bright anode appearance.
[0031] In some possible implementations, in the aluminum alloy, X is Ni, B and Li, and the mass ratio of Cu to Ni, B and Ni is controlled to be: Cu: Ni: B: Li = (0.75-2.0): (0.6-1.2): (0.2-0.4): (0.4-0.7). Within this composition mass ratio range, the aluminum alloy can obtain an excellent elastic modulus, as well as good yield strength, tensile strength and elongation, so that the aluminum alloy exhibits toughness and can obtain a bright anode appearance.
[0032] In some possible implementations, the aluminum alloy includes an Al matrix and second-phase particles dispersed in the Al matrix, the Al matrix is formed of Al element, and the second-phase particles are formed of at least two elements selected from the group consisting of Al element, Mg element, Si element, Cu element, Mn element, and X element. For example, the second-phase particles may be Al12 Mg 17 The second phase particles may be Al-Ni particles, Mg2Si particles, ternary particles formed by Al-Cu-Mg, or particles doped with Mn in the above particles. Exemplarily, when the X element is Ni, the second phase particles may be Al-Ni particles. When the X element is B, the second phase particles may be Al-B particles. When the X element is Li, the second phase particles may be Al-Li particles. When the X element is Ni, B and Li, the second phase particles may be Al-Ni particles, Al-B particles and Al-Li particles.
[0033] In some possible implementations, in the cross section of the aluminum alloy, within 0.05 mm 2 Within the cross-sectional area, the number of second phase particles with a diameter of ≥10 μm is ≤20, which can ensure that the second phase particles are completely dissolved during anodizing and do not affect the high-brightness anode appearance of the aluminum alloy.
[0034] The present application also provides a method for preparing the aluminum alloy, comprising:
[0035] S1. Take the raw materials of the aluminum alloy according to the composition of the aluminum alloy, melt and cast to obtain an ingot. Exemplarily, the aluminum alloy raw material corresponding to the Mg element in the aluminum alloy is Al-Mg master alloy, the aluminum alloy raw material corresponding to the Si element is Al-Si master alloy, the aluminum alloy raw material corresponding to the Cu element is Al-Cu master alloy, the aluminum alloy raw material corresponding to the Mn element is Al-Mn master alloy, the aluminum alloy raw material mainly corresponding to the Al element is pure Al ingot, the aluminum alloy raw material corresponding to the Ni element is Al-Ni master alloy, the aluminum alloy raw material corresponding to the B element is Al-B master alloy, and the aluminum alloy raw material corresponding to the Li element is Al-Li master alloy.
[0036] S2. subjecting the ingot to homogenization annealing treatment.
[0037] S3, extruding the ingot that has been subjected to homogenization annealing treatment to obtain an extruded material.
[0038] S4. Performing aging treatment on the extruded material to obtain an aluminum alloy.
[0039] Among them, in some possible implementations, step S2 is specifically: keeping the ingot at 570° C. to 620° C. for 3 h to 8 h to perform homogenization annealing treatment.
[0040] In some possible implementations, in step S3, the ingot subjected to homogenization annealing is extruded at an ingot temperature of 520°C to 570°C, an extrusion speed of 5m / min to 15m / min, and an outlet temperature of 530°C to 560°C to obtain an extruded material.
[0041] In some possible implementations, in step S4, the extruded material is kept at 150° C. to 225° C. for 5 h to 12 h for aging treatment.
[0042] In some possible implementations, between step S3 and step S4, the following further step is included: S31, pre-deforming the extruded material.
[0043] In some possible implementations, after step S4, the method further includes: S5, performing cold deformation processing on the aluminum alloy.
[0044] Among them, both step S31 and step S5 can improve the toughness of the aluminum alloy.
[0045] The properties of the aluminum alloy provided in this application are described below in conjunction with specific embodiments.
[0046] Comparative Examples 1 to 4 and Examples 1 to 24 all provide an aluminum alloy, and the components of the aluminum alloy are shown in Table 1. Among them, the impurity elements in the aluminum alloys of Comparative Examples 1 to 4 and Examples 1 to 24 include Ti, Cr and Fe.
[0047] Table 1 Composition of aluminum alloys of Comparative Examples 1-4 and Examples 1-24
[0048]
[0049]
[0050] The aluminum alloy provided in Example 1 is prepared according to the following steps:
[0051] S1. Weighing raw materials of aluminum alloy according to the components of aluminum alloy in Table 1 and performing melting and casting to obtain an ingot;
[0052] S2, keeping the ingot at 620°C for 3h for homogenization annealing;
[0053] S3, extruding the ingot subjected to homogenization annealing at an ingot temperature of 570° C., an extrusion speed of 15 m / min, and an outlet temperature of 560° C. to obtain an extruded material;
[0054] S31, pre-deforming the extruded material;
[0055] S4, keeping the extruded material treated by S31 at 225° C. for 5 hours for aging treatment to obtain an aluminum alloy;
[0056] S5. Perform cold deformation processing on the aluminum alloy.
[0057] The raw materials of the aluminum alloy in Example 1 include Al-Mg master alloy, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy and pure Al ingot.
[0058] The aluminum alloy provided in Example 2 is prepared according to the following steps:
[0059] S1. Weighing raw materials of aluminum alloy according to the components of aluminum alloy in Table 1 and performing melting and casting to obtain an ingot;
[0060] S2, keeping the ingot at 600°C for 5 hours for homogenization annealing;
[0061] S3, extruding the ingot subjected to homogenization annealing at an ingot temperature of 550° C., an extrusion speed of 10 m / min, and an outlet temperature of 540° C. to obtain an extruded material;
[0062] S31, pre-deforming the extruded material;
[0063] S4, keeping the extruded material treated by S31 at 175° C. for 8 hours for aging treatment to obtain an aluminum alloy;
[0064] S5. Perform cold deformation processing on the aluminum alloy.
[0065] The raw materials of the aluminum alloy in Example 2 include Al-Mg master alloy, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy and pure Al ingot.
[0066] The aluminum alloy provided in Examples 3-24 has the same preparation steps as Example 2, except that the raw materials of the aluminum alloy in Examples 3-5 and Examples 14-16 include Al-Mg master alloy, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-Ni master alloy and pure Al ingot, the raw materials of the aluminum alloy in Examples 6-8 and Examples 17-19 include Al-Mg master alloy, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-B master alloy and pure Al ingot, the raw materials of the aluminum alloy in Examples 9-11 and Examples 20-22 include Al-Mg master alloy, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-Li master alloy and pure Al ingot, and the raw materials of the aluminum alloy in Examples 12-13 and Examples 22-24 include Al-Mg master alloy, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-Ni master alloy, Al-B master alloy, Al-Li master alloy and pure Al ingot.
[0067] The aluminum alloy provided in Comparative Example 1 was prepared according to the following steps:
[0068] S1. Weighing raw materials of aluminum alloy according to the components of aluminum alloy in Table 1 and performing melting and casting to obtain an ingot;
[0069] S2, keeping the ingot at 570°C for 8h for homogenization annealing;
[0070] S3, extruding the ingot subjected to homogenization annealing at an ingot temperature of 520° C., an extrusion speed of 5 m / min, and an outlet temperature of 510° C. to obtain an extruded material;
[0071] S31, pre-deforming the extruded material;
[0072] S4, keeping the extruded material treated by S31 at 150° C. for 12 hours for aging treatment to obtain an aluminum alloy;
[0073] S5. Perform cold deformation processing on the aluminum alloy.
[0074] Among them, the raw materials of the aluminum alloy in Comparative Example 1 include Al-Mg master alloy, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy and pure Al ingot.
[0075] The aluminum alloys provided in Comparative Examples 2-4 have the same preparation steps as those in Example 2, except that the raw materials of the aluminum alloy in Comparative Example 2 include Al-Mg master alloy, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-Ni master alloy and pure Al ingot. The raw materials of the aluminum alloy in Comparative Example 3 include Al-Mg master alloy, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-B master alloy and pure Al ingot. The raw materials of the aluminum alloy in Comparative Example 4 include Al-Mg master alloy, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-Li master alloy and pure Al ingot.
[0076] The aluminum alloys of Examples 1 to 24 and Comparative Examples 1 to 4 were used to measure the performance parameters of the aluminum alloys. The results are shown in Table 2. The performance parameter test of the aluminum alloy includes: measuring the 0.05 mm 2 The number of second phase particles with a diameter ≥ 10 μm in the cross-sectional area is used to determine the room temperature mechanical properties of the aluminum alloy and observe the anode appearance of the aluminum alloy.
[0077] Table 2 Performance parameters of aluminum alloys of Examples 1 to 24 and Comparative Examples 1 to 4
[0078]
[0079]
[0080] As can be seen from Table 1 and Table 2, the aluminum alloys provided in Examples 1 to 24 have a high-brightness, slightly numbness, or slightly numbness and dumbness anode appearance effects, so that the shell made of the aluminum alloy has a good anode appearance effect, which is beneficial for application in terminal equipment. At the same time, the elastic modulus of the aluminum alloys of Examples 1 to 24 is relatively high, which is beneficial for improving the elastic modulus of the shell made of the aluminum alloy, and has a good application prospect in the terminal equipment. The embodiments of the present application are carried out through a large number of experiments, and the experimental results show that by controlling 0.7%≤Mg≤1.1%, 0.5%≤Si≤1.1%, 0.5%≤Cu≤4.5%, 0<Mn≤0.9%, 0≤X<6%, 85.7%≤Al≤98.3%, and the total content of inevitable impurity elements in the aluminum alloy is ≤1.0%, the obtained aluminum alloy has a good anode appearance effect and can also have a high elastic modulus.
[0081] Among them, compared with the aluminum alloys without adding X element in Examples 1 to 2, the aluminum alloys in Examples 3 to 24 all added X element, and the elastic modulus of the obtained aluminum alloys was higher than that of the aluminum alloys in Examples 1 and 2, and the lowest elastic modulus could reach 76 GPa. The experimental results show that by adding X element to the aluminum alloy, the elastic modulus of the aluminum alloy can be improved.
[0082] By comparing Comparative Examples 2 to 4 with Examples 2 to 13, although the aluminum alloys in Comparative Examples 2 to 4 have X element added, the amount of X element added is as high as 6.0%, and the obtained aluminum alloy presents a numb and dull anode appearance effect. The experimental results show that although the addition of X element is beneficial to improve the elastic modulus of the aluminum alloy, too much X element is not conducive to the aluminum alloy presenting a bright anode appearance effect. In some embodiments, the content of X element in the aluminum alloy is: 0≤X<6%.
[0083] In addition, by comparing Comparative Example 1 with Examples 1 to 2, the amount of Mg element added to the aluminum alloy of Comparative Example 1 is 1.3%, which exceeds 1.1%, and the obtained aluminum alloy presents a numb and dull anode appearance effect. The possible reason is that excessive Mg content leads to an increase in the insoluble Mg2Si phase formed by Mg and Si elements, thereby significantly reducing the anode appearance effect of the aluminum alloy, which is not conducive to the shell made of the aluminum alloy to present a better anode appearance effect.
[0084] By comparing Examples 14 to 16, 17 to 19, or 20 to 22, by increasing the Cu content in the aluminum alloy, the elastic modulus of the aluminum alloy is gradually increased, the yield strength and tensile strength are gradually increased, and the elongation is gradually increased, showing better toughness. At the same time, by comparing Examples 3 to 5, 6 to 8, or 9 to 11, by increasing the content of the X element in the aluminum alloy, the elastic modulus of the aluminum alloy is gradually increased, and the yield strength and tensile strength are gradually increased. The embodiments of the present application have been verified through a large number of experiments, and controlling the aluminum alloy to 0.5% ≤ Cu ≤ 3.0%, 1.0% ≤ X ≤ 5.5% can ensure that the aluminum alloy has an excellent elastic modulus, as well as a higher yield strength and tensile strength, and the aluminum alloy exhibits toughness. Furthermore, controlling the aluminum alloy to 0.6%≤Cu≤2.0%, 1.0%≤X≤2.0% can ensure that the aluminum alloy has excellent elastic modulus, as well as higher yield strength and tensile strength. While the aluminum alloy exhibits strong toughness, it can also ensure that the aluminum alloy has a bright anode appearance.
[0085] By comparing Examples 3 to 5 and Examples 14 to 16, when the X element added to the aluminum alloy is Ni, the anode appearance effect, elastic modulus, yield strength, tensile strength and elongation of the aluminum alloy can be adjusted by adjusting the mass ratio of Cu to Ni. The embodiments of the present application have been verified through a large number of experiments that the mass ratio of Cu to Ni is controlled to be: Cu: Ni = (0.75-2.0): (1.0-2.0), which can ensure that the aluminum alloy can obtain excellent elastic modulus, as well as good yield strength, tensile strength and elongation, and the aluminum alloy exhibits toughness, and the aluminum alloy can also obtain a bright anode appearance effect.
[0086] By comparing Examples 6 to 8 with Examples 17 to 19, when the X element added to the aluminum alloy is the B element, the anode appearance effect, elastic modulus, yield strength, tensile strength and elongation of the aluminum alloy can be adjusted by adjusting the mass ratio of Cu to B elements. The embodiments of the present application have been verified through a large number of experiments that the mass ratio of Cu to B elements is controlled to be: Cu: B = (0.75-2.5): (1.0-2.0), which can ensure that the aluminum alloy can obtain excellent elastic modulus, as well as good yield strength, tensile strength and elongation, and the aluminum alloy exhibits toughness, and the aluminum alloy can also obtain a bright anode appearance effect.
[0087] By comparing Examples 9 to 11 with Examples 20 to 22, when the X element added to the aluminum alloy is Li, by adjusting the mass ratio of Cu to Li, the anode appearance, elastic modulus, yield strength, tensile strength and elongation of the aluminum alloy can be adjusted. The embodiments of the present application have been verified through a large number of experiments that the mass ratio of Cu to Li is controlled to be: Cu: Li = (0.75-2.0): (1.0-2.0), which can ensure that the aluminum alloy can obtain excellent elastic modulus, as well as good yield strength, tensile strength and elongation, and the aluminum alloy exhibits toughness, and the aluminum alloy can also obtain a bright anode appearance.
[0088] By comparing Examples 12 to 13 with Examples 23 to 24, when the X element added to the aluminum alloy is Ni, B and Li, by adjusting the mass ratio of Cu to Ni, B and Li, the anode appearance, elastic modulus, yield strength, tensile strength and elongation of the aluminum alloy can be adjusted. The embodiments of the present application have been verified by a large number of experiments, and the mass ratio of Cu to Ni, B and Ni is controlled to be: Cu: Ni: B: Li = (0.75-2.0): (0.6-1.2): (0.2-0.4): (0.4-0.7), which can ensure that the aluminum alloy can obtain excellent elastic modulus, as well as good yield strength, tensile strength and elongation, and the aluminum alloy exhibits toughness, and the aluminum alloy can also obtain a bright anode appearance.
[0089] In addition, by comparing Comparative Examples 2 to 4 with Examples 1 to 24, in the cross section of the aluminum alloys of Comparative Examples 2 to 4, the thickness of 0.05 mm 2 In the cross-sectional area, the number of second phase particles with a diameter of ≥10 μm is greater than or equal to 24, and the obtained aluminum alloy presents a numb and dull anode appearance effect, which is a poor anode appearance effect. In the cross-sectional area of the aluminum alloys of Examples 5, 8, 11, 16, 19 and 22, the 0.05 mm 2 In the cross-sectional area, the number of second phase particles with a diameter of ≥10 μm is greater than 20 and less than 24, and the obtained aluminum alloy presents a slightly numb or slightly numb and dull anode appearance effect, and the anode appearance effect of the aluminum alloy is relatively poor. 2 The number of second phase particles with a diameter of ≥10 μm in the cross-sectional area is ≤20, and the obtained aluminum alloys all present a bright anode appearance. 2 Within the cross-sectional area of the aluminum alloy, the number of second phase particles with a diameter ≥10μm is ≤20, which can ensure that the second phase particles are completely dissolved during the anodizing process of the aluminum alloy and does not affect the bright anode appearance of the aluminum alloy.
[0090] What is disclosed above is only a preferred embodiment of the present application, and it certainly cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiments and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.
Claims
1. An aluminum alloy, characterized in that: Calculated by the mass of the aluminum alloy, the components of the aluminum alloy include: 0.7%≤Mg≤1.1%, 0.5%≤Si≤1.1%, 0.5%≤Cu≤4.5%, 0<Mn≤0.9%, 0≤X<6%, 85.7%≤Al≤98.3%, and the total content of inevitable impurity elements ≤1.0%, wherein the X element is selected from at least one of Ni element, B element, and Li element.
2. The aluminum alloy according to claim 1, characterized in that X is a Ni element, and the mass ratio of the Cu to the Ni element is: Cu:Ni=(0.75-2.0):(1.0-2.0).
3. The aluminum alloy according to claim 1, characterized in that X is the B element, and the mass ratio of the Cu to the B element is: Cu:B=(0.75-2.5):(1.0-2.0).
4. The aluminum alloy according to claim 1, characterized in that X is a Li element, and the mass ratio of the Cu to the Li element is: Cu:Li=(0.75-2.0):(1.0-2.0).
5. The aluminum alloy according to claim 1, characterized in that X represents Ni element, B element and Li element, and the mass ratio of Cu to the Ni element, the B element and the Ni element is: Cu:Ni:B:Li=(0.75-2.0):(0.6-1.2):(0.2-0.4):(0.4-0.7).
6. The aluminum alloy according to any one of claims 1 to 5, characterized in that: The aluminum alloy includes an Al matrix and second phase particles dispersed in the Al matrix, the Al matrix is formed of Al element, and the second phase particles are formed of at least two elements selected from the group consisting of Al element, Mg element, Si element, Cu element, Mn element and X element.
7. The aluminum alloy according to claim 6, characterized in that In the cross section of the aluminum alloy, within 0.05mm 2 Within the cross-sectional area, the number of second phase particles with a diameter ≥10 μm is ≤20.
8. The aluminum alloy according to any one of claims 1 to 5, characterized in that: The inevitable impurity elements include at least one of Ti element, Cr element and Fe element.
9. The aluminum alloy according to any one of claims 1 to 5, characterized in that: 0.5%≤Cu≤3.0%, 1.0%≤X≤5.5%.
10. The aluminum alloy according to claim 9, characterized in that 0.6%≤Cu≤2.0%, 1.0%≤X≤2.0%.
11. A housing, characterized in that: The shell is made of the aluminum alloy according to any one of claims 1 to 10.
12. A terminal device, characterized in that: It comprises a display screen and a shell as claimed in claim 11, wherein the display screen is mounted on the shell.
13. The terminal device according to claim 12, characterized in that: The terminal device is a mobile phone, and the shell is a middle frame of the mobile phone; or, the terminal device is a tablet computer, and the shell is a middle frame of the tablet computer; or, the terminal device is a computer, and the shell is a shell of the computer.
Citation Information
Cited By
Composite material and preparation method therefor, plate body, housing assembly, and electronic device
WO2026166113A1